2015
DOI: 10.1037/adb0000039
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use longitudinally predicts adjustment and impairment in college students with ADHD: The role of executive functions.

Abstract: The primary aim of this study was to evaluate whether alcohol consumption longitudinally predicts the adjustment, overall functioning, and grade point average (GPA) of college students with ADHD and to determine whether self-report of executive functioning (EF) mediates these relationships. Sixty-two college students comprehensively diagnosed with ADHD completed ratings at the beginning and end of the school year. Regression analyses revealed that alcohol consumption rated at the beginning of the year signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Moreover, research has found that ADHD symptoms in conjunction with executive function deficits in college students are associated with a number of risky behaviors including alcohol use (Langberg, Dvorsky, Kipperman, Molitor, & Eddy, 2014; Rooney, Chronis-Tuscano, & Huggins, 2012), and risky sexual behavior (Golub, Starks, Kowalczyk, Thompson, & Parsons, 2012). It is plausible that executive function deficits lead to impaired decision-making, which, in turn, may lead to unsafe sexual behavior and substance use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, research has found that ADHD symptoms in conjunction with executive function deficits in college students are associated with a number of risky behaviors including alcohol use (Langberg, Dvorsky, Kipperman, Molitor, & Eddy, 2014; Rooney, Chronis-Tuscano, & Huggins, 2012), and risky sexual behavior (Golub, Starks, Kowalczyk, Thompson, & Parsons, 2012). It is plausible that executive function deficits lead to impaired decision-making, which, in turn, may lead to unsafe sexual behavior and substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the results from the present study suggest college students with ADHD are more likely to struggle with attention, planning, and organization, skills that are critical for college student success, thereby placing these students at increased risk for academic and psychosocial difficulties (Advokat et al, 2011; Heiligenstein, Guenther, Levy, Savino, & Fulwiler, 1999; Murphy, Barkley, & Bush, 2002; Pope, 2010; Schwanz, Palm, & Brallier, 2007; Weyandt et al, 2013; Wolf et al, 2009). Moreover, research has found that ADHD symptoms in conjunction with EF deficits in college students are associated with a number of risky behaviors including alcohol use (Langberg, Dvorsky, Kipperman, Molitor, & Eddy, 2015; Rooney, Chronis-Tuscano, & Huggins, 2015), and risky sexual behavior (Golub, Starks, Kowalczyk, Thompson, & Parsons, 2012). It is plausible that EF deficits lead to impaired decision-making, which, in turn, may lead to unsafe sexual behavior and substance use.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of anxiety, depression, daytime sleepiness, suicide, self-injurious behaviors, physical illness, decreased physical activity, risky sexual behavior, increased cigarette smoking, alcohol and drug dependency, and severity of work performance difficulties are very common among students with ADHD in college (Baker, Prevatt, & Proctor, 2012; Glass & Flory, 2012; Goniu & Moreno, 2013; Huggins, Rooney, & Chronis-Tuscano, 2015; Langberg, Dvorsky, Becker, & Molitor, 2014; Langberg, Dvorsky, Kipperman, Molitor, & Eddy, 2015; Martino & Advokat, 2004; Meinzer, Hill, Pettit, & Nichols-Lopez, 2015; Mesman, 2015; Nelson & Gregg, 2012; Patros et al, 2013; Prevatt, Dehili, Taylor, & Marshall, 2015; Shifrin et al, 2010; Van Eck et al, 2015; Van Eck, Markle, Dattilo, & Flory, 2014). It is found that the discovery and intervention of ADHD during college can decrease the incidence, severity, and duration of future mental health problems, including major depressive disorder, anxiety disorders, and substance abuse (Nelson & Gregg, 2012; Prevatt et al, 2015; Rooney, Chronis-Tuscano, & Yoon, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…College students who have experienced abuse or other interpersonal violence earlier in life are at risk for not only PTSD but also for complex trauma symptoms related to affect dysregulation (Ford et al, 2006; Kaltman et al, 2005) that have been associated with increased risk of problem drinking and decreased use of protective behavior strategies among college students (Bogg, Lasecki, & Vo, 2016; N. Clarke et al, 2016; Langberg, Dvorsky, Kipperman, Molitor, & Eddy, 2015; Linden-Carmichael, Braitman, & Henson, 2015). As proposed in the 11 th Edition of the International Classification of Diseases, there is evidence that adolescents with trauma histories may experience complex trauma symptoms involving disturbances of self-organization often co-occur with, but are distinct from, the symptoms of PTSD (Sachser, Keller, & Goldbeck, 2017).…”
Section: The Potential Role Of Complex Trauma In College Student Probmentioning
confidence: 99%